2016
DOI: 10.1136/bcr-2016-216722
|View full text |Cite
|
Sign up to set email alerts
|

Vertical muscle transposition with silicone band belting in VI nerve palsy

Abstract: A woman aged 60 years developed a Millard-Gubler syndrome after a diagnosis of a cavernous angioma in the median and paramedian areas of the pons. In this context, she presented a right VI nerve palsy, right conjugate gaze palsy, facial palsy and left hemiparesis. To improve the complete VI nerve palsy, we planned a modified transposition approach, in which procedure we made a partial transposition of vertical rectus with a silicone band that was fixated posteriorly. After the procedure, the patient gained the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…Our patient had a full recovery within one week of presentation. This is consistent with the clinical course described in case reports, especially those involving small acute infarcts [2,4,6,7,9,10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our patient had a full recovery within one week of presentation. This is consistent with the clinical course described in case reports, especially those involving small acute infarcts [2,4,6,7,9,10].…”
Section: Discussionsupporting
confidence: 91%
“…Millard-Gubler syndrome, also known as ventral pontine syndrome or facial abducens hemiplegia syndrome, was first described in 1858, and was classically associated with a pontine mass [8]. Subsequent reports, however, have involved cases caused by bleeding and infarcts, and rarely neurocysticercosis [2][3][4][5][6][7]9,10]. The lesion lies above the level of the decussation of the pyramidal and spinothalamic tracts.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by paralysis affecting the face and the abducent nerve on the side of the lesion and central hemiplegia on the opposite side[1]. It has been reported that MGS could be found in patients with brainstem tumor such as cavernous angioma[2-4], rimary meningeal hemangiopericytoma[5], neurocysticercosis[6]. As far as we know, only five cases of MGS caused by cerebral infarction have been reported[1,7-10].…”
Section: Introductionmentioning
confidence: 99%
“… 76 The vertical muscles can also be united together without attaching to LR, using direct nonabsorbable suture or silicone band, with or without LR plication. 77 78 The results of different muscle union procedures are available in Table 5 .…”
Section: R Esultsmentioning
confidence: 99%